Peptide Transporter OsNPF8.1 Contributes to Sustainable Growth under Salt and Drought Stresses, and Grain Yield under Nitrogen Deficiency in Rice - Qiu Diyang; Hu Rui; Li Ji; Li Ying; Ding Jierong; Xia Kuaifei; Zhong Xuhua; Fang Zhongming; Zhang Mingyong (Rice Science, 2023)
Peptide transport is important for plant tissues where rapid proteolysis occurs, especially during germination and senescence, to enhance redistribution of organic nitrogen (N). However, the biological role of peptide transporters is poorly investigated in rice. We characterized the function of the peptide transporter OsNPF8.1 of rice nitrate transporter 1/peptide transporter family (NPF). Ectopic expression of OsNPF8.1 in yeast revealed that OsNPF8.1 encoded a high-affinity di-/tri-peptide transporter, and the osnpf8.1 mutants had a lower uptake rate of the fluorescent-labelled dipeptide c in leaves of rice seedlings. Histochemical assays showed that OsNPF8.1 was highly expressed in mesophyll cells and vascular parenchyma cells, but not detected in root hairs and epidermises. Expression of OsNPF8.1 was induced by N deficiency, drought, NaCl and abscisic acid, and kept at a high level in senescing leaves. Under N deficiency conditions, compared with the wild type Zhonghua 11, the osnpf8.1 mutants grew slower at the seedling stage, and had lower grain yield and lower N content in the grains. In contrast, OsNPF8.1-over-expressing rice (OsNPF8.1-OE) grew faster at the seedling stage and had a higher grain yield. The osnpf8.1 seedlings were less tolerant to salt and drought stresses. These results suggested that stress-induced organic N transportation mediated by OsNPF8.1 might contribute to balance plant growth and tolerate to salt/drought stress and N-deficiency.